Aquafeed Biofloatation through Mycelial Hydrophobic Coating - Liza Nurohmah; Catur Sriherwanto; Imam Suja’i; Etyn Yunita (Journal of Aquaculture and Fish Health, 2023)
Aquafeed biofloatation through tempeh mould fermentation on sinking aquafeeds produces water-floating property, an alternative to the expensive extrusion technique. However, the role of the fungal mycelium in this biofloatation remains unclear.  This study aimed to investigate the role of surface mycelium of the fermented feed in the buoyancy. Commercial sinking feed was fermented using a tempeh starter at ambient temperature (28–33 °C) for 48 h. Freshly fermented feeds were produced, some of which were peeled to remove the surface mycelium, while the others were left intact. After 24-h oven-drying at 50 °C, physical tests were done on the peeled and unpeeled fermented feeds, plus unfermented feed as a negative control. Results showed that the unpeeled fermented feed had the highest floatability (48% at the 60th minute), and continued floating until the 120th minute with 36% floatability. In contrast, the unfermented feed did not float at all, while the peeled fermented feed sank within the first 2 minutes. Only the unpeeled fermented feed showed hydrophobic characteristics (> 90° contact angle and 20.16 s water absorption time). Thus, the hydrophobic surface mycelium might prevent rapid water infiltration into the fermented feed matrix, enabling the intact fermented feed to float longer.